2002
DOI: 10.1002/ajh.10059
|View full text |Cite
|
Sign up to set email alerts
|

CD30 and the NPM‐ALK fusion protein (p80) are differentially expressed between peripheral blood and bone marrow in primary small cell variant of anaplastic large cell lymphoma

Abstract: The t(2;5)(p23;q35) translocation results in the formation of a unique chimeric NPM-ALK protein (p80). Expression of this protein is considered to be one of the clinical features of anaplastic large cell lymphoma (ALCL). Recently recognized as one clinical subtype of ALCL, the small cell variant is prone to have a leukemic presentation. Although the small cell variant has been recognized as a subtype of ALCL, the clinical properties of this subtype, especially the immunophenotype of lymphoma cells in periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Interestingly, two cases showed variable expression of CD30. This feature has been described previously, 4 and in cases with leukaemic presentation the CD30– cells may specifically represent the leukaemic component. In all cases ALK was uniformly positive in most tumour cells, both in the small and large tumour cells with a variable pattern of granular and diffuse cytoplasmic immunopositivity, with or without nuclear expression.…”
Section: Summary Of Clinical Casessupporting
confidence: 74%
“…Interestingly, two cases showed variable expression of CD30. This feature has been described previously, 4 and in cases with leukaemic presentation the CD30– cells may specifically represent the leukaemic component. In all cases ALK was uniformly positive in most tumour cells, both in the small and large tumour cells with a variable pattern of granular and diffuse cytoplasmic immunopositivity, with or without nuclear expression.…”
Section: Summary Of Clinical Casessupporting
confidence: 74%
“… 9 , 18 So far a total of 26 cases of leukemic ALCL have been identified, mostly presenting with an elevated white blood cell count (average <100 × 10 9 /L). 6 , 8 , 9 , 10 , 12 , 13 , 14 , 17 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 Clinically, most patients presented with B-type symptoms, with fever being reported most (85.18%). The age of affected patients ranged from seven months to 63 years, but with 70% being younger than 30 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…In our review of the literature we have identified only 20 cases of ALCL with a leukemic phase (Table 1). [5][6][7][8][9][10][11][12][13][14][15][16][17] Typically, patients present with an elevated WBC count <100 ¥ 10 9 /L.…”
mentioning
confidence: 99%